TLR7 Negatively Regulates B10 Cells Predominantly in an IFNγ Signaling Dependent Manner - Chodisetti, Sathi Babu; Fike, Adam J.; Domeier, Phillip P.; Choi, Nicholas M.; Soni, Chetna; Rahman, Ziaur S. M. (Frontiers in Immunology, 2020)
IL-10 producing B cells (B10 cells) play an important immunoregulatory role in various autoimmune and infection conditions. However, the factors that regulate their development and maintenance are incompletely understood. Recently, we and others have established a requirement for TLR7 in promoting autoimmune antibody forming cell (AFC) and germinal center (GC) responses. Here we report an important additional role of TLR7 in the negative regulation of B10 cell development. TLR7 overexpression or overstimulation promoted the reduction of B10 cells whereas TLR7 deficiency rescued these cells in both non-autoimmune and autoimmune-prone mice. TLR7 expression was further inversely correlated with B cell-dependent IL-10 production and its inhibition of CD4 T cell proliferation and IFNg production in an in vitro B cell and T cell co-culture system. Further, B10 cells displayed elevated TLR7, IFNgR and STAT1 expression compared to non B10 cells. Interestingly, deficiency of IFNgR in TLR7 overexpressing lupus-prone mice rescued B10 cells from TLR7-mediated reduction. Finally, B cell intrinsic deletion of IFNgR was sufficient to restore B10 cells in the spleens of TLR7-promoted autoimmune mouse model. In conclusion, our findings demonstrate a novel role for the IFNgR-STAT1 pathway in TLR7-mediated negative regulation of B10 cell development.